Post-process treatments on supersonic cold sprayed coatings : a review - Sun, Wen (2021)
Cold Gas Dynamic Spray or Supersonic Cold Spray, or simply ‘Cold Spray’, is an emergingtechnology for rapidly building thin films, thick coatings and large-scale additive manufacturing atrelatively low temperatures. In a cold spray process, particles are accelerated to supersonic speedsby a propellant gas and impact a substrate, thus producing a strong bonding with the substrateand subsequently forming a deposit via layer-by-layer buildup. The scalability and low cost of thismethod make it promising for many applications in industry, such as metal component surfacerepair/enhancement/restoration and functional coatings for electrical, thermal, biomedical, energystorage, and nuclear plant applications. However, cold sprayed deposits usually require post processtreatments to further modify their microstructures and mechanical properties in order to obtain thedesired performances. A number of studies have been carried out on this topic. Here, recent progressin different post process treatments on cold sprayed deposits is reviewed, including heat treatment,friction-stir processing, shot peening, and laser re-melting. The effects of these post treatments on themicrostructure, residual stress and mechanical properties of cold sprayed deposits are discussed.